2020
DOI: 10.3390/en13236195
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Studies of the Influence of Dynamic Loading on the Elastic Properties of Sandstone

Abstract: Under dynamic loading, the geomechanical properties of porous clastic rocks differ from those in quasistatic loading. A small experimental rig was built to directly assess the influence of vibrations on the uniaxial compressive strength (UCS), Young modulus, and Poisson’s ratio. A piezoelectric actuator powered by a signal from an oscillator was used in the rig as a generator of vibrations. A laser sensor and eddy current probe measured the longitudinal and transverse deformation. Tinius Hounsfield and Instron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…Nonstationary loading of the samples revealed nonlinearity in the behavior of the dynamic modulus of elasticity. Moreover, if in the region of higher frequencies (from 10 Hz to 60 Hz) the test results confirmed the previously obtained dispersion of Young's modulus according to the power law (see, for example, [24][25][26][27][28]), then in the region of low frequencies (less than 10 Hz) it was revealed that Young's modulus changes according to the kind of logarithmic law. Figure 15 shows an example of a dynamic test for the sample 2/6.…”
Section: Dependence Of An Elasticity Modulus On the Dynamic Load Freq...supporting
confidence: 82%
See 2 more Smart Citations
“…Nonstationary loading of the samples revealed nonlinearity in the behavior of the dynamic modulus of elasticity. Moreover, if in the region of higher frequencies (from 10 Hz to 60 Hz) the test results confirmed the previously obtained dispersion of Young's modulus according to the power law (see, for example, [24][25][26][27][28]), then in the region of low frequencies (less than 10 Hz) it was revealed that Young's modulus changes according to the kind of logarithmic law. Figure 15 shows an example of a dynamic test for the sample 2/6.…”
Section: Dependence Of An Elasticity Modulus On the Dynamic Load Freq...supporting
confidence: 82%
“…Energies 2021, 14, x FOR PEER REVIEW 15 of 20 modulus according to the power law (see, for example, [24][25][26][27][28]), then in the region of low frequencies (less than 10 Hz) it was revealed that Young's modulus changes according to the kind of logarithmic law. Figure 15 shows an example of a dynamic test for the sample 2/6.…”
Section: Dependence Of An Elasticity Modulus On the Dynamic Load Freq...mentioning
confidence: 99%
See 1 more Smart Citation
“…Several mechanisms of the nonlinear nature of Young's modulus were proposed, as reviewed in [22], but much more experimental research is still required. The results presented in this study are of a major project focusing on investigating the mechanical properties of rocks, the preliminary results of which have been presented in [23].…”
Section: Introductionmentioning
confidence: 99%
“…The results reported by Kozhevnikov et al [3] and Guzev et al [4] indicated an increase in the Young's modulus of sandstone with increasing values of dynamic load and frequency. Accordingly, an increase RESEARCH NOTE in the frequency of impact leads to the strengthening of rocks and a decrease in the likelihood of the formation of new cracks and voids [5,6].…”
Section: Introductionmentioning
confidence: 99%